Benefits of Quality Control Circle (QCC) and Proposed Applications in the Defense Industry: A Literature Review - Setiawan, Benny; Soediantono, Dwi (International Journal of Social and Management Studies, 2022)
The purpose of this article is to explore the benefits of implementing Quality Control Circle (QCC) in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 24 international journal articles published from 2015 to 2021 regarding the implementation of the Quality Control Circle (QCC) in various industrial sectors and the defense industry. The analysis used used 25 content analysis of journal articles, then coding was carried out on the contents of the reviewed journals. The data that had been collected was then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of the Quality Control Circle (QCC) can improve quality, productivity, delivery, cost, morale and occupational safety and health in various industries so that the Quality Control Circle (QCC) method is recommended to be applied in the defense industry. Based on the literature review, the quality control circle (QCC) is recommended to be applied to the defense industry.